Quantitative and Qualitative Determination of Gliotoxin and Acetaldehyde Toxins in Yeasts Isolated from some Respiratory Patients and Study of Yeast Resistance to some Antibiotics - Iman. H. Al Fayyadh; Mohammed Hashim al-Yasiri (Indian Journal of Forensic Medicine & Toxicology, 2022)
The concentrations (64, 128, 32, 16, 8, 4, 2, 1, 0.5, 0.25 and 0.125) mg/ml were used to calculate the lowestinhibitory concentration of antibiotics for Candida yeast by microdilution method. The antibiotics fluconazoleand itraconazole were used to complete this experiment, which is based on the results of testing the API Candidasystem by demonstrating the resistance of yeasts using several mechanisms, which serve to phenotype eachorganism selected in the framework. In this test, it was found that there is resistance to the antibiotics itraconazoleand fluconazole in the types of yeasts under experiment. The toxin-producing yeasts extracted from yeasts showedthat the toxin-producing yeast species were only 27 out of 30 samples of yeast, despite the growth efficiency of allsamples. While 30 samples of yeast isolated from patients’ sputum, it was found that all samples under the currentstudy contain different amounts of acetaldehyde toxins with different concentrations.